2020
DOI: 10.1007/s42452-020-03489-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer flows of immiscible fractional second grade fluids in a rectangular channel

Abstract: Multi-layer laminar unsteady flows of immiscible fractional second grade fluids in a rectangular channel made by two parallel plates are studied. The fluid motion is produced by the motion of parallel walls in their plane and by the timedependent pressure gradient in the presence of the linear fluid-fluid interface conditions. The mathematical model is based on the generalized constitutive equations for the shear stress described by the time-fractional Caputo derivative. Integral transforms (finite Fourier sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The exact solution is acquired via Laplace transform (LT). References 6 , 7 investigated of fractional immiscible multi-layer flow of second-grade fluid in rectangular channel. The remedy is acquired via finite Fourier sine and LT. Siddique et al 8 studied the heat transfer analysis of fractional second-grade fluid with Newtonian heating.…”
Section: Introductionmentioning
confidence: 99%
“…The exact solution is acquired via Laplace transform (LT). References 6 , 7 investigated of fractional immiscible multi-layer flow of second-grade fluid in rectangular channel. The remedy is acquired via finite Fourier sine and LT. Siddique et al 8 studied the heat transfer analysis of fractional second-grade fluid with Newtonian heating.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the heat transfer in ordinary fluids is higher than those of thermal memory fluids; however, the memory parameters affect the fluids' velocities as accelerating factors. Some other important multilayer flow problems are studied in [14][15][16]. The parallel flow of the fractional Maxwell fluid inside a cylindrical domain has been studied by Rauf et al [17] in the presence of pressure gradient in the flow direction.…”
Section: Introductionmentioning
confidence: 99%